From Trust Antecedents to Trust Frameworks: Co-Creating Multi-Actor Agreements for Data Sharing - van der Peet, Louise; Bharosa, Nitesh; Janssen, Marijn (Conference on Digital Government Research, 2025)
Companies and public agencies who are looking to improve their services can benefit from more data sharing. However, due to regulations and security concerns, data sharing between individuals, businesses and public agencies is complicated. There are many variables to consider in a multi-actor environment where actors with various roles and incentives look for legal and technical certainty. Public and private organizations increasingly acknowledge the need for multi-organizational agreements on data sharing standards. This results in the rise of trust frameworks to guide efforts towards trustworthy data sharing in an interorganizational setting. However, academic literature on trust frameworks is scarce, and we lack a systematic understanding of the factors that constitute trust in a multi-actor data sharing environment. The objective of this paper is to provide a systematic understanding of the antecedents of trust playing a role in trust frameworks. A two-stage approach is followed, starting with a systematic review of antecedents, followed by an empirical inquiry as verification. Our findings indicate a wide range of antecedents - including technological and organizational antecedents - can be considered.